Mixed Finite Element Computation of Energy Release Rate in Anisotropic Materials Based on Virtual Crack Closure-Integral Method - Sami Derouiche; Salah Bouziane; Hamoudi Bouzerd (Fracture and Structural Integrity)
The material with anisotropic properties are becoming widely essential due to the ease to manipulate their mechanical properties in order to obtain a particular quality, insure safety or a specific behavior. Those kind of materials are considered anisotropic because their characteristics and behavior are dependent to every direction of the material’s orientation.